Trame Verte et Bleue : Utilisation des cartes d’occupation du sol pour une première approche qualitative de la biodiversité - Sandrine Liénard; Philippe Clergeau (Cybergeo)
The need to integrate individual movements of species and their different dispersions is becoming urgent in biodiversity conservation, especially in our countries which are more and more fragmented. The conclusions of the recent “Grenelle de l’Environnement” in France have joined the previous results in landscape ecology research that analyses relationships between species dispersion and structures of geographic areas. One of the difficulties is the choice of a method able to traduce the green and blue network in useful maps, especially at a regional level. We propose here a simple and rapid method of assessment of potential biodiversity based on weight given by experts to different landscape occupations of a database. The approach is tested on the “Mode d’Occupation du Sol” database (scale of 1/5 000) of Île-de-France region. Identification of habitats and their potential biodiversity allows us to roughly but quickly characterize the biodiversity of territories and to identify the potential green and blue networks. Maps obtained here show interesting paths to the beginning of a discussion about biodiversity and we suggest that this kind of precise map has to be promoted in each region.